Latihan postgraduate Diploma In Teaching (PGDip) dalam kalangan pensyarah Unimas - Hafizah, Binti Abu Bakar (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to assess training in teaching postgraduate Diploma (PGDip) among Unimas lecturer. This study used qualitative research methods and using semi-structured interviews. Findings indicate that the objectives and issues raised at the beginning of the study has already been answered positively overall. This means there has been a change and improvement in training postgraduate teaching diploma (PGDip). The study's findings are helpful for lecturers who attended PGDip training as a training aid for lecturers or the CALM PGDip providing training to be more effective, providing new exposure for guest lecturers with postgraduate training in teaching diploma (PGDip) among lecturers in Unimas and evaluate the effectiveness of the training and PGDip may be a reference to future researchers to study of more related issues.